Six ways to maximize survey response rates: Lessons from a medical school accreditation survey in a Canadian setting - Javidan, Arshia Pedram; Rai, Yeshith; Cheung, Jeffrey; Patel, Raumil V; Kulasegaram, Kulamakan Mahan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Background: Surveys are being increasingly used to gather feedback and study data in healthcare professions. However, it may be challenging to achieve high response rates in surveys administered to healthcare professionals. The aim of this paper is to report six strategies that contributed to a high response rate on the Independent Student Analysis at the University of Toronto (U of T), which can be applied to other surveys to achieve strong response rates amongst healthcare professionals.Methods: In 2019, as part of accreditation for the U of T MD Program, we conducted the Independent Student Analysis, a student-led survey examining a medical student’s experience. We review and critically evaluate the factors that contributed to a robust response rate amongst one of the largest cohorts of medical students in Canada.Results: Among 1080 students in the MD program, we achieved an unprecedented response rate of 87.2%. Six factors were identified that most contributed to our high response rate, including: faculty support, student representation, eliciting participant feedback, creating protected time for completion, offering incentives, and generating awareness.Conclusions: Eliciting high survey response rates from medical learners can be challenging. However, with careful consideration of learner feedback and effective employment of the strategies discussed in this paper, medical school faculty may better engage students in survey completion, achieving higher response rates and gathering richer insight, which can be used to more effectively enact meaningful change amongst healthcare professionals.